(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
In this article, the authors analyze the legal status of the National Academy of Sciences of the Kyrgyz Republic, which has undergone repeated perturbations over the years of independence. Finally, the Constitution of the Kyrgyz Republic (May 5, 2021) defines the constitutional status of the NAS as a state body coordinating the development of fundamental and applied science in the country. However, in the Law “On Science”, the Academy is still considered the highest state scientific institution, and the coordinating role is assigned to the Ministry of Education and Science, which contradicts the Basic Law of the state. And the Law “On the National Academy of Sciences of the Kyrgyz Republic” has not yet been adopted due to bureaucratic red tape. The authors believe that the NAS, as written in the Constitution, should become the central state body responsible for the development and implementation of scientific and technical policy in the country.